Biochemical effects of induced neurotoxicity by methyl bromide in rats - Zahraa Mohammed. Jasim; Rana Abdulla Salih (University of Thi-Qar Journal of agricultural research, 2022)
Bromide and chloride are chemically related halide elements that the kidney works with to keep the overall body halide content balanced. Also Bromide is a element that known to cause many neurotoxic and other organs toxicity such as GIT tract , respiratory tract and liver. Therefore, we aimed in the present study on the effect of bromide at daily intake doses to investigate possible neurotoxic effect and modulate its possible mechanism by measuring the oxidant and antioxidant impact in brain and Ameliorative trail of Sodium chloride .Chloride-containing diuretics, such as sodium chloride, increase bromide elimination in the urine.Key word: neurotoxicity , methyl bromide , Rat .